Inhibition of Klebsiella pneumoniae adhesion in mice enterocytes by antibodies of hemagglutinin pili protein with MW 12.8 kDa of Klebsiella pneumoniae - Agustina, Dini; Retoprawiro, Sumarno; AS, Noorhamdani (Journal of Tropical Life Science, 2014)
Klebsiella pneumoniae as one of the most common cause of VAP is also the second most common cause of community- and hospital-acquired gram negative bloodstream infection. The process of infection caused by direct contact with infectious agents begins with the host cell adhesion process either by pili or by afimbria adhesin (AFA). There were no reported researches on the hemagglutinin pili protein of K.pneumoniae as adhesion factors.This study was conducted in order to determine the hemagglutinin pili protein of K.pneumoniae, polyclonal antibody produced from pili protein immunization, and its ability to inhibit K.pneumoniae adhesion in mice enterocytes. Adhesion inhibition test used HA antibody with the implementation of dose dilutions of 1/100, 1/200, 1/400, 1/800, 1/1600, 1/3200 and 0 (control). While immunocytochemistry test used HA pili protein with the implementation of dose dilutions of 1/10000, 1/20000, 1/40000, 1/80000, 1/160000, 1/320000 and 0 (control). Hemagglutinin pili protein found in K.pneumoniae had MW 12.8 kDa. Pearson correlation analysis of adhesion test showed there were significant correlation between antibody dilution titer with bacterial adhesion (p = 0.032, R = -0.797). Furthermore, Anova analysis of IT showed that there were significant differences between the various dilution titer with antigen-antibody reaction (p=0.000). Antibody of hemagglutinin pili protein with MW 12.8 kDa of K.pneumoniae can inhibit the adhesion of K.pneumoniae to the enterocytes of mice.